Trend of BS 8900: 2006 Guidance for Managing Sustainable Development Application in Thai Logistics Service Providers - Ponanake, Pareeyawadee (Information Management and Business Review, 2014)
The research aimed to study 1) the opinions of Thai logistics provider towards BS8900:2006 Guidance for Managing Sustainable Development and 2) the trend of Thai logistics providers towards the application of BS8900:2006 Guidance for Managing Sustainable Development. Populations were Freight Forwarding service providers on the list of Thailand’s logistics service providers for freight forwarding service and TIFFA including international logistics company i.e. UPS, DHL, TNT and FedEX. The sample groups were random by multi stage sampling. The size of sample group was 168 persons. The research methods were questionnaires which were analyzed by percentage, Mean, Standard Deviation, and inferential statistics perfuming by Logistic Regression. The research found that 1) the opinions of Thai logistics providers towards BS8900:2006 Guidance for Managing Sustainable Development was strongly agreement 2) The probability of application of BS8900:2006 Guidance for Managing Sustainable Development was increased 2.134 times and the accuracy of forecast was 84.5%